Can Coordination‐Driven Supramolecular Self‐Assembly Reactions Be Conducted from Fully Aliphatic Linkers?. Issue 3 (12th December 2017) - Elsayed Moussa, Mehdi; Evariste, Sloane; Krämer, Barbara; Réau, Régis; Scheer, Manfred; Lescop, Christophe
Abstract: The reaction between a preassembled Cu I bimetallic molecular clip with a short intermetallic distance and a series of fully aliphatic cyano‐capped ditopic linkers with increasing lengths was investigated. It is shown that, depending on the length of the ditopic linkers, the rational design of unprecedented supramolecular compact metallacycles containing fully aliphatic walls is possible. The specific preorganized molecular arrangement of the molecular clip used favors stabilizing interlinker London dispersion interactions, which allow, as the length of the linkers increases, the selective formation of discrete compact metallacycles at the expense of 1D coordination polymers. The generalizability of this approach was demonstrated by the reaction of fully aliphatic cyano‐capped linkers with two other types of preassembled Cu I bimetallic molecular clips that also had short intermetallic distances. Abstract : Give them a sense of direction : Cyano‐capped fully aliphatic linkers underwent supramolecular assembly with preorganized Cu I dimers with short intermetallic distances to form different types of metallacycles and 1D coordination polymers depending on the length of the linkers (see picture). Stabilizing London dispersion interactions between the methylene units made the selective self‐assembly of such linkers with nondirectional backbones possible.